IDENTITY CRISIS IN PAUL KALANITHI’S NOVEL WHEN BREATH BECOMES AIR - Habib, Sarwan; Ekalestari, Susi (Universitas Islam Sumatera Utara, 2024)
An identity crisis, a prevalent social phenomenon, can manifest in individuals at any stage of life within society. This study explores the protagonist's struggle with identity in Paul Kalanithi's When Breath Becomes Air, aiming to identify and elucidate the types of identity crises encountered. Drawing upon identity crisis theories proposed by Erikson and Baumeister, et al., the researchers employ descriptive qualitative analysis to examine and interpret the novel. The findings of the research reveal several facets of the protagonist's motivation crisis. Firstly, the causes of Paul's motivation crisis stem from his battle with liver cancer. Secondly, Paul undergoes a range of subjective experiences, including vacillating commitment, confusion about values, regular bouts of vagueness, feelings of emptiness, and self-unconsciousness, as well as anxiety. Furthermore, the study highlights various behaviors exhibited by Paul amidst his identity crisis. These include comparing his activities as a doctor and as a patient, viewing the world through the contrasting lenses of hope and death, and grappling with a sense of hopelessness as his dreams, hard work, and life choices are shattered. Overall, the research sheds light on the complexity of identity crises and their profound impact on individuals, as exemplified through the protagonist's journey in When Breath Becomes Air.